The Introduction of the Global Traditional, Complementary, and Integrative Healthcare (TCIH) Research Agenda on Antimicrobial Resistance and Its Added Value to the WHO and the WHO/FAO/UNEP/WOAH 2023 Research Agendas on Antimicrobial Resistance - Erik W. Baars; Petra Weiermayer; Henrik P. Szőke; Esther T. van der Werf (Antibiotics)
Background/Objectives: Given the magnitude and urgency of the global antimicrobial resistance (AMR) problem and the insufficiency of strategies to reduce antimicrobial use, there is a need for novel strategies. Traditional, Complementary, and Integrative Healthcare (TCIH) provides strategies and solutions that contribute to reducing (inappropriate) antimicrobial use, preventing or treating infections in both human and veterinary medicine, and may contribute to promoting the health/resilience of humans and animals and reducing AMR. The aims of this study were to present the core results of a global TCIH research agenda for AMR and its added value to two existing global AMR research agendas published in 2023. Methods: A survey, interviews, and consensus meetings among network members, as an adapted version of the nominal group technique, were executed to develop the global TCIH research agenda. A comparison of the global TCIH research agenda with the two existing global AMR research agendas was performed. The TCIH additions to these two existing global AMR research agendas were determined. Results: The global TCIH research agenda adds to 19 of 40 research priorities of the World Health Organization (WHO) AMR research agenda 2023 and three of the five pillars of the WHO/Food and Agriculture Organization of the United Nations (FAO)/United Nations Environment Programme (UNEP)/World Organisation for Animal Health (WOAH) research agenda 2023. In addition, the TCIH research agenda adds two new research themes with four new research priorities and three new research priorities to already existing themes of the two global AMR research agendas. Conclusions: The global TCIH research agenda fits with and adds to two global AMR research agendas and can be used as an additional strategy to reduce AMR and (inappropriate) use of antibiotics.